A study of the impact of staggered boards on corporate financialization: from the perspective of board governance - Cao, Chongyan; Zhang, Yutong (Frontiers in Psychology, 2024)
This empirical study investigates how staggered boards affect corporate financialization in China's capital market by analyzing a sample of A-share listed companies from 2011 to 2020, with a specific focus on board governance mechanisms. The results indicate that implementing staggered boards significantly increases levels of corporate financialization. On the one hand, the implementation of a staggered board structure can exacerbate the speculative mindset and profit-driven behavior among board members, leading management to prioritize financial investments for personal gain. On the other hand, a staggered board system may also amplify managerial laziness, potentially incentivizing them to rely heavily on financial investments in order to swiftly achieve performance targets with minimal effort. Furthermore, both managerial ownership and audit supervision are found to be critical factors in mitigating this positive impact and preventing excessive financial investment behavior. Digital transformation can also significantly inhibit the promotion effect of staggered board on corporate financialization. Additionally, heterogeneity analysis reveals that both company ownership structure and industry competition intensity have an influence on the relationship between staggered boards and corporate financialization. This paper offers guidance on comprehending the applicability of staggered board provisions and mitigating financial risks in enterprises.